Diagnostic and therapeutic role of non-coding RNAs regulating programmed cell death in melanoma - Wang, Zixu; Xie, Cong; Chen, Xiao (Frontiers in Oncology, 2024)
lncRNAs (long non-coding RNAs) are heterogeneous RNA molecules that modulate various cellular processes, such as proliferation, differentiation, migration, invasion, and apoptosis, via different mechanisms. An increasing amount of research indicates that abnormal expression of lncRNA influences the development of drug resistance as well as the genesis and advancement of cancer, including melanoma. Furthermore, they are attractive biomarkers for non-invasive cancer diagnostics due to their strongly modulated expression and improved tissue and disease specificity. This review offers a succinct overview of the present understanding concerning the potential diagnostic biomarker potential of lncRNAs in melanoma. Cell death occurs frequently during growth and throughout life and is an active, organized, and genetically determined process. It is essential for the regulation of homeostasis. Controlled cell death and non-programmed cell death are both forms of cell death. The most prevalent forms of regulatory cell death are pyroptosis, ferroptosis, autophagy, necroptosis, necrosis, and apoptosis. Ferroptosis, pyroptosis, and autophagy are less common forms of cell death compared to necrosis, apoptosis, and necroptosis. ncRNAs are regulatory RNA molecules that are not involved in encoding proteins. They primarily consist of circular RNAs (circ RNAs), lncRNAs, and microRNAs (miRNAs). Moreover, non-coding RNAs have the ability to modulate tumor cell autophagy, pyroptosis, and ferroptosis at the transcriptional or post-transcriptional stage, as well as function as oncogenes and tumor suppressor genes, which can have considerable effects on the incidence and growth of tumors. This review concentrated on the recent advancements in the research of the diagnostic and therapeutic functions of ncRNAs in the regulation of programmed cell death in melanoma.